Challenges faced by the food industry under franchising sector. (2022) - Chacko, Susan; Sumathi, R.; Narayanan, M.K. Badri; Syam Narayanan, S.
Abstract: Franchising is a competitive business strategy to expand the market. In the food industry franchising is considered as a unique strategy to expand its operations in different geographical areas. In India, 15% of the franchises fail in the initial years of their business. This paper aims to identify the challenges faced by the food franchises concerning the Chennai region. Semi-structured interviews were conducted with company executives, academicians and researchers to identify the challenges which pose a great threat to the food franchises. Nine challenges were identified from the data collected. The challenges identified were customer satisfaction, human resource, economic aspect, competition landscape, incorporation, innovation, resource and capabilities, supply chain management and government regulatory measures and ecosystem. Interpretive structural modeling (ISM) method is used to identify the most challenging factor which poses a great threat to the food franchise. The finding reveals that government regulatory measures and ecosystem is the most challenging factor in the franchised food sector.